CORRELATION OF CHOLESTEROL LEVELS, BLOOD GLUCOSE, URIC ACID AND AGES - Siagian, Ernawaty; Ramschie, Putri Agape; Lappra, Karenina Gabriela (Fakultas Keperawatan, Universitas Klabat, 2025)
Metabolic syndrome and cardiovascular disease are often associated with elevated serum lipid, glucose, and uric acid levels. When these conditions occur together, they significantly increase the risk of heart disease, stroke, and type 2 diabetes, especially in individuals in the productive age range. This study was conducted to evaluate the association between cholesterol, blood sugar levels, uric acid concentrations, and age variables. The methodology in this study was descriptive correlational using a purposive sampling technique. This study selected Wiyono Village and Taman Sari Village, Gedung Tataan District, Pesawaran Regency, Lampung, as the research area. A total of 110 adult residents were involved in this study. Univariate and bivariate analyses were performed. Data collection included blood sampling to obtain cholesterol, uric acid, and blood glucose levels. After the results were obtained, each respondent received counseling on a healthy lifestyle (NEWSTART) according to the results of each respondent's examination by health workers. Revealing a statistically significant (sig value 0.023 <0.05) between cholesterol and uric acid. A sig value of 0.019 < 0.05 indicates a significant correlation between cholesterol and blood sugar. A sig value of 0.015 < 0.05 indicates a significant correlation between age and uric acid. Lifestyle management is essential as a preventative measure for increased lipid, glucose, and hyperuricemia levels. Sindrom metabolik dan penyakit kardiovaskular sering dikaitkan dengan peningkatan kadar lipid, glukosa, dan asam urat serum. Bila kondisi ini terjadi bersamaan, secara signifikan meningkatkan risiko penyakit jantung, stroke, dan diabetes tipe 2 terutama pada individu dalam rentang usia produktif. Studi ini dilakukan untuk mengevaluasi keterkaitan antara kolesterol, kadar gula darah, konsentrasi asam urat, serta variabel usia. Metodologi dalam penelitian ini adalah deskriptif korelasional dengan menggunakan teknik purposive sampling. Penelitian ini memilih Desa Wiyono dan Desa Taman Sari, Kecamatan Gedung Tataan, Kabupaten Pesawaran, Lampung, sebagai daerah penelitian. Sebanyak 110 penduduk dewasa terlibat dalam penelitian ini. Analisis univariat dan analisis bivariat dilakukan. Pengumpulan data meliputi pengambilan sampel darah untuk mendapatkan kadar kolesterol, asam urat, dan glukosa darah. Setelah hasilnya diperoleh, setiap responden menerima konseling tentang gaya hidup sehat (NEWSTART) sesuai dengan hasil pemeriksaan setiap responden oleh tenaga kesehatan. Mengungkapkan signifikan secara statistik (nilai sig 0,023 < 0,05) antara kolesterol dan asam urat. Nilai sig 0,019 < 0,05 antara kolesterol dan gula darah. Nilai sig 0,015 < 0,05 signifikan antara usia dan asam urat. Manajemen gaya hidup perlu diperhatikan sebagai langkah pencegahan peningkatan kadar lipid, glukosa dan hiperurisemia